2023
DOI: 10.1108/wje-09-2022-0372
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the effects of luminaire installation geometries and other factors on road illumination system photometric parameters and energy efficiency

Abstract: Purpose Properly planned road illumination systems are collectively a public wealth and the commissioning of such systems may require extensive planning, simulation and testing. The purpose of this simulative work is to offer a simple approach to facilitate luminance-based road lighting calculations that can be easier to comprehend and apply to practical designing problems when compared to complex multi-objective algorithms and other convoluted simulative techniques. Design/methodology/approach Road illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Studies have shown that a lower lumen output of LED lamps is sufficient to match higher lumen values from HPSV lamps (Brons et al, 2021). Modeling techniques on comparison of HPSV and LED luminaires concluded that LEDs are marginally higher in average luminance per watt increment of luminaire power than HPSV luminaires (Bhattacharya et al, 2023). Studies on the photometric impact of replacing the original light source are limited (Abdullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a lower lumen output of LED lamps is sufficient to match higher lumen values from HPSV lamps (Brons et al, 2021). Modeling techniques on comparison of HPSV and LED luminaires concluded that LEDs are marginally higher in average luminance per watt increment of luminaire power than HPSV luminaires (Bhattacharya et al, 2023). Studies on the photometric impact of replacing the original light source are limited (Abdullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research explores successful SSL implementation in outdoor lighting systems [21]. LED technology shows positive results [20], not only from the point of view of energy efficiency but also in terms of the improvement in the quality of illumination [4], which can be shown in parameters such as the uniformity of the illuminated surfaces [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the designing of indoor environments with daylight integration (for example, historical buildings and public libraries), light shelves are often installed (to redirect sunlight into the interior space) whose upper reflective surfaces are coated with highly reflective film in aluminium alloy (Balocco and Calzolari, 2008) and the daylight transmission level through a clerestory increases with the increment in the optical reflectance of the reflective surface of a light shelf (Bhattacharya et al , 2022). Moreover, it is averred that for road lighting systems, where installation layouts and pavement characteristics profoundly influence the photometric quality parameters and system energy efficiency (Bhattacharya et al , 2021; Bhattacharya et al , 2023), aluminium-coated reflectors of luminaires reduce lumen depreciation and can increase luminaire luminous efficacy (luminous flux emitted by the luminaire per Watt of consumed electric power) (Unlu, 2022). Consequently, it can be avouched that aluminium alloys do find a plethora of energy-efficient applications in different fields ranging from lighting design to production.…”
Section: Introductionmentioning
confidence: 99%